2006
DOI: 10.1038/sj.cdd.4401846
|View full text |Cite
|
Sign up to set email alerts
|

Differential susceptibility to TRAIL of normal versus malignant human urothelial cells

Abstract: Comparing normal human urothelial (NHU) cells to a panel of six representative urothelial cell carcinoma (UCC)-derived cell lines, we showed that while TRAIL receptor expression patterns were similar, susceptibility to soluble recombinant crosslinked TRAIL fell into three categories. 4/6 carcinoma lines were sensitive, undergoing rapid and extensive death; NHU and 253J cells were partially resistant and HT1376 cells, like normal fibroblasts, were refractory. Both normal and malignant urothelial cells underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 42 publications
6
23
1
Order By: Relevance
“…In addition, the HT1376 cell line appears to have a lower level of apoptotic proteins. Also post gemcitabine sensitization, TRAIL can induce a rapid negative-feedback loop that could downregulate TRAIL receptor expression thus allowing tumour cells to escape TRAIL mediated effect (28). In addition, we observed in this and other studies (unpublished data), that TRAIL can trigger the intrinsic pathway via Bid and that this pathway may be hampered or impaired in TRAIL-resistant UC cells.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, the HT1376 cell line appears to have a lower level of apoptotic proteins. Also post gemcitabine sensitization, TRAIL can induce a rapid negative-feedback loop that could downregulate TRAIL receptor expression thus allowing tumour cells to escape TRAIL mediated effect (28). In addition, we observed in this and other studies (unpublished data), that TRAIL can trigger the intrinsic pathway via Bid and that this pathway may be hampered or impaired in TRAIL-resistant UC cells.…”
Section: Discussionsupporting
confidence: 69%
“…In some experiments we observed that UC cell lines that are less responsive to TRAIL express DR4 and DR5 receptors at levels comparable to the TRAIL-sensitive ones (data not shown). That is, the apoptotic sensitivity of the UC cells did not appear to be related to the DR expression patterns alone (27)(28)(29). Thus, our current observation that TRAIL induced apoptosis in a caspase- dependent fashion may suggest that resistance to TRAIL may depend more on the level of intracellular signalling molecules rather than differences in receptor expression.…”
Section: Discussionmentioning
confidence: 68%
“…T2 (T cell) and K562 (CML) cell lines were grown in RPMI 1640 (Life Technologies), 10% FCS (Harlan Sera-Labs), and 1% glutamine (Life Technologies). Bladder tumor cell lines EJ, RT112, and 253J cells were grown in a 50:50 ratio of RPMI 1640:DMEM (Life Technologies), 5% FCS and 1% glutamine; SW480 cells (colorectal tumor cells) were grown in DMEM, 10% FCS, and 1% glutamine; parental RT112 and SW480 cell lines were transduced to express CD40 using a retroviral vector (16,17). Human foreskin fibroblast (HFF) and normal human urothelial (NHU) cells were grown as previously described (16).…”
Section: Cd14mentioning
confidence: 99%
“…In several types of cancers, increased c-FLIP expression is correlated with resistance to TRAIL-, Fas-, or TNF-induced apoptosis (17)(18)(19)41,42). Post-translational modification and degradation of c-FLIP as well as increased mRNA levels have been suggested to be involved in increasing c-FLIP expression (43).…”
Section: Discussionmentioning
confidence: 99%
“…Both c-FLIP S and c-FLIP L are recruited to the DISC where c-FLIP L is cleaved into a p43 intermediate form, which, together with c-FLIP S , remains in the DISC where they inhibit caspase-8 cleavage (16). c-FLIP is expressed in various cancers and its expression is associated with enhanced tumorigenicity and poor clinical outcome in many types of cancers because of chemotherapeutic drug and TRAIL resistance (17)(18)(19).…”
mentioning
confidence: 99%